Additional new records of host plant for Clethrogyna turbata (Erebidae) - Lee Gerald Zheng Yang; Maria Lourdes Lardizabal; Kee Yong Hao; Berhaman Ahmad (Forest Research Centre, Sabah Forestry Department, 2025)
Clethrogyna turbata is a tussock moth in the family of Erebidae. This species had been recorded as polyphagous, which Holloway (1999) summarized over 28 host plant species from various plant families, including Anacardiaceous, Brassicaceae, Cycadaceae, Dipterocarpus, Euphorbiaceous, Geraniaceae, Poaceae, Fabaceae, Asparagaceae, Lythraceous, Morceau, Myrtaceous, Nelumbonaceae, Solanaceae and Verbenaceae. More new records of host plants for C. turbata were published including Ixora coccinea and Axon opus compress us (Chung, 2003), Terminalia Copeland (Chung et al. 2006), Bauhinia Blakean (Chung et al. 2009), four species of Shorea (Chung et al. 2013) and Neolamarckia macrophylla (Chung et al. 2016). Besides, over 37 species of host plants for C. turbata were listed in Robinson et al. (2023). Observation of Clethrogyna turbata defoliating activities In December 2022, an estimated 100 C. turbata caterpillars were spotted feeding on Terminalia catappa L. and Terminalia mantaly H. Perrier (both Combretaceae) at the nursery of Faculty Tropical Forestry, Universiti Malaysia Sabah.